GA-NIFS: JWST/NIRSpec integral field unit observations of HFLS3 reveal a dense galaxy group at z ∼6.3 - Jones, GC; Übler, H; Perna, M; Arribas, S; Bunker, AJ; Carniani, S; Charlot, S; Maiolino, R; Rodríguez Del Pino, B; Willott, C; Bowler, RAA; Böker, T; et al. (EDP Sciences, 2024)
Massive, starbursting galaxies in the early Universe represent some of the most extreme objects in the study of galaxy evolution. One such source is HFLS3 (z ∼ 6.34), which was originally identified as an extreme starburst galaxy with mild gravitational magnification (μ ∼ 2.2). Here, we present new observations of HFLS3 with the JWST/NIRSpec integral field unit in both low (PRISM/CLEAR; R ∼ 100) and high spectral resolution (G395H/290LP; R ∼ 2700), with high spatial resolution (∼0.1″) and sensitivity. Using a combination of the NIRSpec data and a new lensing model with accurate spectroscopic redshifts, we find that the 3″ × 3″ field is crowded, with a lensed arc (C, z = 6.3425 ± 0.0002), two galaxies to the south (S1 and S2, z = 6.3592 ± 0.0001), two galaxies to the west (W1, z = 6.3550 ± 0.0001; W2, z = 6.3628 ± 0.0001), and two low-redshift interlopers (G1, z = 3.4806 ± 0.0001; G2, z = 2.00 ± 0.01). We present spectral fits and morpho-kinematic maps for each bright emission line (e.g. [OIII]λ5007, Hα, and [NII]λ6584) from the R2700 data for all sources except G2 (whose spectral lines fall outside the observed wavelengths of the R2700 data). From a line ratio analysis, we find that the galaxies in component C are likely powered by star formation, though we cannot rule out or confirm the presence of active galactic nuclei in the other high-redshift sources. We performed gravitational lens modelling, finding evidence for a two-source composition of the lensed central object and a magnification factor (μ = 2.1 − 2.4) comparable to findings of previous work. The projected distances and velocity offsets of each galaxy suggest that they will merge within the next ∼1 Gyr. Finally, we examined the dust extinction-corrected SFRHα of each z > 6 source, finding that the total star formation (510 ± 140 M⊙ yr−1, magnification-corrected) is distributed across the six z ∼ 6.34 − 6.36 objects over a region of diameter ∼11 kpc. Altogether, this suggests that HFLS3 is not a single starburst galaxy, but instead a merging system of star-forming galaxies in the epoch of reionisation.